IMPACT OF CLOPROSTENOL SODIUM TREATMENT DURING EARLY POST PARTUM PERIOD ON FERTILITY IN DAIRY CATTLE - RAUT, M R; INGAWALE, M V; DESHMUKH, S G; HAJARE, S W; INGOLE, R S (The Indian Journal of Animal Reproduction, 2016)
Normally calved dairy cattle (n=8 in treatment and control group each) were evaluated for the impact of early postpartum treatment (day 0, 5 and 10 post partum) with prostaglandin F2á analogue, cloprostenol sodium, on expulsion ofplacenta, uterine involution, exhibition of first post partum estrus and first service conception rate. Cloprostenol treatedcattle had early expulsion of placenta and uterine involution (p0.05), thus, suggesting the beneficial impact of treatment to a certain extent in dairy cattle
Keywords: Cloprostenol sodium; Cattle,; Estrus; Post partum; Uterus